Formation of RuO2 nanoparticles by thermal decomposition of Ru(NO)(NO3)3. Issue 6 (July 2015) - Petrović, Željka; Ristić, Mira; Marciuš, Marijan; Sepiol, Bogdan; Peterlik, Herwig; Ivanda, Mile; Musić, Svetozar
Abstract: A simple one-pot synthesis of RuO2 nanoparticles by the thermal decomposition of ruthenium nitrosyl nitrate [Ru(NO)(NO3 )3 ] up to 800 °C was investigated. The RuO2 phase was characterized by XRD, SAXS, FE SEM/EDS, Raman, DTA/TGA and FT-IR techniques. Broadening of prominent diffraction lines (110), (101) and (211) was used to estimate nanocrystallite sizes in RuO2 particles. FE SEM showed the formation of RuO2 plates at 400 °C which consisted of RuO2 nanoparticles of about 15–25 nm in size. At 800 °C RuO2 nanoparticles showed the sintering effect and some of them increased in size to about 200 nm. Raman and FT-IR spectra consolidated the findings. Moreover, DTA curves showed the decomposition and release of NO and NO3 − groups to be a stepwise process.